William R. Freudenburg, a life in social research - Maret, Susan (Research in social problems and public policy ;, 2013)
True to the nature of the Gedenkschrift, this commemorative publication celebrates the work of sociologist Dr. William Freudenburg, one of the founding editors of RSPPP and Dehlsen Professor, University of California, Santa Barbara. Chapters include personal reminiscences as well as research that reflect and build on Dr. Freudenburgs theories including recreancy, bureaucratic slippage, his research in environmental disasters, climate change natural resources, technological risk and Scientific Certainty Argumentation Method (SCAM). Government transparency, power and control are also among the topics discussed.